0912 Sleep Diary vs Actigraphy based Outcomes in Adults with Fibromyalgia: Do Opioid Dose and Age Predict Discrepancies?. (27th April 2018) - Curtis, A F; Miller, M B; Boissoneault, J; Robinson, M; Staud, R; Berry, R B; McCrae, C S
Abstract: Introduction: Patients with fibromyalgia frequently experience insomnia. Symptoms assessed via sleep diaries and actigraphy often produce discrepant findings. This study examined whether opioid dose and patient age interact in predicting the magnitude or direction of discrepancy between diary and actigraphy sleep outcomes in adults with fibromyalgia. Methods: Participants ( N =199, 18–77 years of age, M =51.5, SD =11.7) with comorbid fibromyalgia and insomnia completed 14 days of sleep diary and actigraphy. Daily opioid dose was converted to lowest recommend dosage units. Multiple regressions determined whether average opioid dose and its interaction with age predicted magnitude or direction of discrepancy between sleep diary and actigraphy measurements of sleep onset latency (SOL), wake after sleep onset (WASO), and sleep efficiency (SE). Patient sex, use of sleep medication, evening pain, and total sleep time were entered as covariates. Results: Greater opioid dose predicted greater magnitude of discrepancy in SOL ( B =6.10, SE =2.29, p =.008) and SE ( B =1.92, SE =.70, p =.007). Opioid dose interacted with age to predict direction of discrepancy in SOL ( B =.88, SE =.27, p =.001) and SE ( B =-.17 SE =.08, p =.03). For SOL, greater opioid dose predicted longer actigraphy than diary estimates in younger patients ( B =-11.02, SE =4.65, p =.02), longer diary than actigraphy estimates in older patients ( B =9.09, SE =3.66, p =.01), and was not a predictor in middle-aged patients. For SE, greater opioid dose predicted larger diary than actigraphy estimates in younger patients ( B =3.27, SE =1.36 p =.02) and was not a predictor in older/middle-aged patients. Opioid dose did not predict magnitude or direction of WASO discrepancies. Conclusion: Results suggest that in patients with fibromyalgia, the magnitude of diary and actigraphy SOL/SE discrepancies may increase as a function of opioid dose, and the direction of discrepancies may depend on patient age. We speculate that increased opioid use combined with age-related factors such as cognitive decline and increased health problems may impact perceived sleep. Support (If Any): This research was supported by the NIAMS (R01AR055160 and R01AR005160-S1; McCrae, PI). Data were collected as part of clinical trial NCT02001077 SPIN at the University of Florida (McCrae, PI).